Delayed Postoperative Pneumothorax and Pneumomediastinum Following Orthognatic Surgery; a Rare Case Report and Literature Review - R, Mirochnik; M, Joachim; S, Araidy; M, Barak; I, Abu El-Naaj (Archives of Clinical and Medical Case Reports, 2019)
Pneumomediastinum and pneumothorax are potentially life-threatening complications, yet are extremely rare following maxillo-facial surgery. We report a case of a 20-year-old female patient who underwent bilateral sagittal split ramus osteotomy and genioplasty under general anesthesia. Several hours after the completion of the operation, she became extremely dyspneic and was re-intubated in the ward. Chest x-ray and CT exams revealed pneumothorax and pneumomediastinum. A chest drain was introduced and the patient recovered gradually. Here we review the literature and discuss this complication.